The Relationship between Peer Social Support and Stress Levels among the Elderly in the Tresna Werdha Social Institution - Enggal Hadi Kurniyawan; Ahmad Muizzulhafiidh; Erti Ikhtiarini Dewi; Kushariyadi; Latifa Aini Susumaningrum; Fitrio Deviantony; Yeni Fitria (Health and Technology Journal (HTechJ), 2023)
The elderly with cognitive decline becomes more anxious, restless, and socially withdrawn, thus requiring special attention. Social and emotional support and moral and material support provided by relatives and friends will strengthen the elderly's daily lives. This study aims to analyze the relationship between peer social support and stress levels in the elderly. The research design in this study was quantitative analytic with a cross-sectional approach. The sample in this study was 59 elderly living in the Tresna Werdha Social Institution. The measuring tool for this study used a Peer Social Support Questionnaire and the Stress Assessment Questionnaire (SAQ). The correlation test in this study used was the Spearman correlation test. The results of this study indicate that most of the elderly are in the moderate category of stress, with as many as 37 respondents (62.7%), and have peer social support in the positive category, namely 53 respondents (89.8%). Based on the Spearman correlation test, it was found that p-value = 0.001, which means that there is a correlation between peer social support and stress. Spearman's correlation value of -0446 indicates that the direction of the correlation is negative, with the strength of the relationship being. The higher the value of peer social support, the lower the stress on the elderly. Tresna Werdha Social Institution health workers can motivate the elderly so they can increase peer social support and improve programs that benefit the elderly.